The effect of in-office bleaching, at-home bleaching and combination of them on the microchemical structure of enamel with Infrared spectroscopy - K Khosravi; A Aminzade; S Sheikholeslami (Isfahan University of Medical Sciences, 2008)
Introduction: Regarding routine application of bleaching treatment in dental practice, this studyaimed to determine effect of in-office and at-home bleaching and also a combination of methods onhuman enamel, using FT-IR spectroscopy.Method and materials: For fifteen non-carious human molars, after prophylaxis with pumice,each tooth was sectioned bucco-lingually. One pieces of each tooth was bleached. For first groupin-office bleaching, for second group at-home bleaching, and for third group combination of inofficeand at-home bleaching was done. Samples were stored in distilled water. Then enamel ofteeth was powdered with a high-speed rotary instrument. Spectra of powdered enamel were takenfor each sample. The data were analyzed with paired-t and Kruskal-Wallis tests (E = 0.05).Results: On comparing the infrared spectra of non- treated and treated specimens, no structuralchanges were detected in enamel, but the difference in intensity of phosphate between bleachedcontrol sample for in-office bleaching was statistically significant (p value < 0.05). In at-homebleaching and combination of in-office and at-home bleaching, difference in intensity of phosphateand carbonate in treated and non treated specimens was not statistically significant. The differenceof intensity of phosphate and carbonate in 3 groups in samples was not statistically significant.Conclusion: In office bleaching agent was capable of reducing mineral content enamel, which maybe caused by high concentration of carbamide peroxide. There was no reduction in mineral contentof enamel in the presence of fluoride in at-home and combination of at-home and in-officebleaching.Key words: Carbamide peroxide, IR Spectroscopy, Enamel